The Parable of the Slave, Son, and Vineyard: An Early Christian Freedman's Narrative (Hermas "Similitudes" 5.2-11) - Beavis, Mary Ann (The catholic biblical quarterly, 2018)
The Shepherd of Hermas contains a similitude that is very similar to several Synoptic slave parables (Herm. Sim. 5.2-11). Compared to the Gospel parables, however, the similitude ends on a very surprising note: the slave is not only commended by his master but freed and adopted by him. In this essay, I argue that this unexpected outcome can be connected with the identity of Hermas, a Roman freedman—an author whose experience as a manumitted former slave distinctively shapes his telling of the story, which echoes both the Synoptics and Paul. As such, the Hermas similitude is analogous to, but not identical with, the freedom narratives constructed by formerly enslaved African Americans who adjusted and adapted biblical narratives to reflect their own concerns.